Piloting a Nationally Disseminated, Interactive Human Subjects Protection Program for Community Partners: Design, Content, and Evaluation. Issue 2 (10th April 2014) - Solomon, Stephanie; Eakin, Brenda; Kirk, Rosalind; Piechowski, Patricia; Thomas, Barbara
Abstract: Funders, institutions, and research organizations are increasingly recognizing the need for human subjects protections training programs for those engaged in academic research. Current programs tend to be online and directed toward an audience of academic researchers. Research teams now include many nonacademic members, such as community partners, who are less likely to respond to either the method or the content of current online trainings. A team at the CTSA‐supported Michigan Institute for Clinical and Health Research at the University of Michigan developed a pilot human subjects protection training program for community partners that is both locally implemented and adaptable to local contexts, yet nationally consistent and deliverable from a central administrative source. Here, the developers and the analysts of this program discuss its development, its content, and the results of its evaluation.